Model For Heutagogy Design Process With Gamification To Enhance Learning Engagement (HEUG-LEN) - Sazali, Nur Syafiatun Safwana (UTeM, 2019)
Online learning of Massive Open Online Course (MOOC) is e-learning which is web-based learning, distributed learning, and computer-assisted instruction or interned-based learning which is allowing thousands of learners to join any courses anytime and anywhere. MOOC had been widely used by learners a few years back to enhance normal learning in the classroom. The importance of this study is to enhance both learning and engage learners through MOOC gamification and to show that learners can enjoy learning as well as motivating them to participate in each activity provided by their lecturers. In this study, the theory of gamification and heutagogy applied. Following the evolution of education 4.0, learners as connectors, creators, and constructivists, learners must actively participate and engage with all learning activities provided by lecturers. Gamification is the use of game design elements in a non-game context to enhance user engagement while heutagogy is generally a theory of self-learning process to engage the student with learning. This approach can lead students to have their learning besides engaging them to it. Previously, the various approach has been introduced through gamification to engage student learning, but the result of engagement is still slightly weak. Towards the end, the approach introduced has criticism as different courses need different approach or strategies to enhance user engagement. Besides, there are also several studies in theoretically explained how and why they need to implement the game elements to enhance learning engagement, but there is still little empirical evidence on the actual impact. The objectives of this research to propose new learning approach model through gamification to enhance learning engagement and to construct and validate the proposed learning approach to enhance learning engagement through a model called Heutagogy Gamification to Enhance Learning Engagement (HEUG-LEN). This model is implemented using the concept of Self-Learning from Heutagogy process. 77 students are in the experimental group who were taught with HEUG-LEN concept and tested with both with and without gamification applied in their learning activities. Data were using gathered two methods of interview and survey. The finding showed that there are hugely different between both results, which more positive on gamification activities applied and respondents agreed that game elements in MOOC provides more interactive activities. This model will result in contribution both to the knowledge of gamification concept and to implications for practice. Besides, this study also will contribute to the ICT field, especially for MOOC developer in developing learning contents by using this new approach. The outcome of this research expected to the formulation of a gamification model and frameworks which can further expand to a gamified system for online learning. Game elements used in this gamification model are points, mission, and reward.